Why design matters? Making the case for the smaller companies in the automotive industry - Santos, Ricardo Paulo da Silva Cameira dos (2022)
This research focuses on industrial design and strategic management and more specifically on the way the development of design capabilities can influence the strategic product market position of the Portuguese small and medium supply companies for the automotive industry. Industrial design is not usually highlighted as a cornerstone skill of most small-scale automotive supply companies. Instead, it is usually established as a process in resource-capability combinations due to the highly dynamic environments that characterize this industry. Practice suggests a double bias either in the definition of design, sometimes emphasized as style and associated with carmakers, or in design’s role in developing the position of small and medium enterprises in supply networks. This line of reasoning supports the lead research question: why design matters for smaller companies in the automotive industry? The theoretical constructs and context field supported through the literature and the automotive industry profile (international and Portuguese) review reveal a research procedure supported on an interdisciplinary work process. The exploratory nature of this study calls for a qualitative type of research to be conducted as the use of case studies is the most appropriate research strategy. Three firms from the Portuguese automotive cluster were selected for the case study representing an appropriate automotive industry supplier sample for cross-case analysis. The analysis of the gathered data required three phases: analysis and report of individual cases; analysis and report of cross cases; and the conclusions and implications of the cross cases for both theory and practice. As a result, it is revealed the importance of the development of design capabilities for a determined business strategy. The development of design capabilities is key for the development of high added value products for the supply of complex parts or modules. Hence, a list of suggested positive and negative industrial design practices are proposed.